On q-analogue of Janowski-type starlike functions with respect to symmetric points - Khan Muhammad Ghaffar (De Gruyter, 2021)
The main objective of the present paper is to define a class of qq-starlike functions with respect to symmetric points in circular domain. Some interesting results of these functions have been evaluated in this article. The sufficiency criteria in the form of convolutions are evaluated. Furthermore, other geometric properties such as coefficient bounds, distortion theorem, closure theorem and extreme point theorem are also obtained for these newly defined functions.